THE PERSPECTIVE OF PROFESSIONAL FISHERMEN AND LIVE BAIT COLLECTORS ABOUT CLIMATE CHANGE IN THE MIRANDA’S PANTANAL, MATO GROSSO DO SUL STATE (BRAZIL) - Gonçalves, Alexandre Honig (Seven Editora, 2025)
Climate change is already taking place in the Miranda sub-Pantanal and riverside groups historically residing there, such as professional fishermen and live bait collectors, are already feeling these changes, which have a negative and definitive impact on their ways of life and work, putting their immediate livelihoods at risk and, above all, the short future of their traditional crafts and their social-anthropological future linked essentially to the environment. In this article, you will be able to understand how, through applied scientific research, we reached this serious result. DOI: https://doi.org/10.56238/sevened2025.029-043